A high performance wind power generation cable and preparation method thereof

By using modified polyester and modified polyurethane materials in the filling layer materials of wind power cables, combined with additives such as plant nanofiber powder, the problem of unsatisfactory protection of existing cable filling layer materials is solved, and a cable filling layer with high toughness, wear resistance and water resistance is achieved, improving the overall performance of the cable.

CN118942777BActive Publication Date: 2025-03-07GUANGZHOUZHUJIANG CABLE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411353121.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-03-07
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The filling layer material of existing wind power cables has poor protection effect in harsh environments, resulting in poor comprehensive functions of the cable.

Method used

Modified polyester material and modified polyurethane material are used as fill layer materials, and a fill layer with high toughness, wear resistance and water resistance is formed by adding plant nanofiber powder, vulcanizing agent, magnesium oxide and silane coupling agent to the material.

Benefits of technology

It improves the tensile strength, toughness and water resistance of the cable, enhances the stability and service life of the cable in humid environments, and improves the overall performance of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062857530000081
    Figure BDA0005062857530000081
  • Figure BDA0005062857530000091
    Figure BDA0005062857530000091
  • Figure BDA0005062857530000101
    Figure BDA0005062857530000101
Patent Text Reader

Abstract

The present invention belongs to the technical field of cable materials, and specifically relates to a high-performance wind power cable and a preparation method thereof. The filling layer material in the high-performance wind power cable is made of the following raw materials in parts by weight: 60-80 parts of modified polyester material, 20-30 parts of modified polyurethane material, 10-15 parts of vulcanizing agent, 1-5 parts of magnesium oxide, and 1-5 parts of silane coupling agent. The high-performance wind power cable prepared by the present invention has good tensile strength, high toughness, strong water resistance, and also has good distortion resistance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a high-performance wind power generation cable and a preparation method thereof. Background Art

[0002] Power generation cables are mainly composed of cable cores (conductors and insulation layers), sheaths and other parts, and are used to transmit and distribute electrical energy. The cable core of the cable is mainly composed of multiple core wires consisting of an internal conductor and an external insulating layer. Gaps will appear in the cable core during the cabling process, reducing the life of the cable during use. Therefore, a filling layer is usually provided outside the insulating layer. Its main function is to provide support for the cable. Therefore, the role of the filling material is particularly important in the use of the cable. Due to the harsh wind farm environment and the twisting of the power generation cable as the impeller swings, wind power generation cables generally have higher requirements. The protective effect of the filling layer material of the power generation cable in the prior art is often not ideal, resulting in poor comprehensive cable functions.

[0003] The Chinese patent application document with publication number CN107353494A discloses a method for preparing a filling layer material for electric vehicle charging pile cables. The patent uses formaldehyde to react with phenol, and grinds and combines with mica powder and vitrified microbeads in the presence of sodium dodecylbenzene sulfonate, and then makes a filling layer material with main ingredients such as modified polypropylene and diatomaceous earth. The obtained filling layer material has a smooth surface, high hardness and excellent thermal stability, long service life, and excellent tensile strength and impact strength. However, the filling layer material has poor water resistance, which brings hidden dangers to the product. Summary of the invention

[0004] Existing cables have the problem of poor comprehensive performance. In order to solve this problem, the present invention provides a high-performance wind power generation cable and a preparation method thereof.

[0005] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a high-performance wind power generation cable, the high-performance wind power generation cable comprising a core wire, the core wire comprising a conductor, the outer surface of the conductor being coated with an inner shielding layer, an insulating layer and an outer shielding layer in sequence along its own axial direction; a plurality of core wires are twisted along the cable axis to form a cable core, a wrapping tape and an outer sheath are arranged in sequence outside the cable core, and a filling layer is filled between the wrapping tape and the cable core;

[0007] The filling layer material is made of the following raw materials in parts by weight: 60-80 parts of modified polyester material, 20-30 parts of modified polyurethane material, 10-15 parts of vulcanizing agent, 1-5 parts of magnesium oxide, and 1-5 parts of silane coupling agent.

[0008] Preferably, the preparation method of the modified polyester material comprises the following steps:

[0009] (1) mixing plant nanofiber powder and anhydrous ethanol evenly, adding a silane coupling agent, heating under reflux reaction, and drying after the reaction to obtain modified plant nanofiber powder;

[0010] (2) Pentaerythritol, 1,3-acetone dicarboxylic acid dimethyl ester and citrate are uniformly mixed, the temperature is raised to carry out a first-stage reaction, the modified plant nanofiber powder and the catalyst are added, the temperature is continued to be raised to carry out a second-stage reaction, and the modified polyester material is obtained by vacuum curing.

[0011] Preferably, in the step (1), the mass ratio of plant nanofiber powder to silane coupling agent is 1:0.6-0.8; the reaction temperature is 80-90°C, and the reaction time is 2-4h.

[0012] Preferably, the plant nanofiber powder is selected from one of wood fiber powder, bamboo fiber powder and straw fiber powder.

[0013] Preferably, in the step (2), the molar ratio of pentaerythritol to 1,3-acetone dicarboxylic acid dimethyl ester is 1:1.6-2.2; the amount of the citrate ester is 1%-3% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester, the amount of the modified plant nanofiber powder is 10%-15% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester, and the amount of the catalyst is 0.08%-0.15% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester.

[0014] Preferably, in step (2), the temperature of the first stage reaction is 90-100° C., and the time of the first stage reaction is 1-2 h; the temperature of the second stage reaction is 110-130° C., and the time of the second stage reaction is 5-7 h.

[0015] Preferably, in step (2), the citrate ester is trimethyl citrate, triethyl citrate or tributyl citrate; and the catalyst is tetrabutyl titanate, tetraisopropyl titanate or tetrapropyl titanate.

[0016] Preferably, the preparation method of the modified polyurethane material comprises the following steps:

[0017] 1-3 parts by mass of modified cellulose, 10-15 parts by mass of polytetrahydrofuran and 1-2 parts by mass of dodecanediamine are uniformly mixed at a temperature of 80-100° C., 6-10 parts by mass of aromatic diisocyanate and 0.02-0.05 parts by mass of catalyst are added, reacted for 6-8 hours, and vacuum cured to obtain a modified polyurethane material.

[0018] Preferably, the method for preparing the modified cellulose comprises the following steps:

[0019] The plant cellulose is placed in an alkaline solution, heated to 90-110°C, reacted for 10-20 hours, washed with water 2-5 times, placed in an acidic solution at 50-70°C, reacted for 5-10 hours, washed with water 2-5 times, and dried to obtain modified cellulose;

[0020] Wherein, the alkaline solution is a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution;

[0021] The acidic solution is an oxalic acid aqueous solution or an acetic acid aqueous solution.

[0022] Preferably, the plant cellulose is wood fiber, bamboo fiber or straw fiber.

[0023] Alkaline solution can loosen the cellulose structure, and then treating the alkali-treated cellulose with acidic solution can promote the hydrolysis of cellulose.

[0024] Preferably, the aromatic diisocyanate is 4,4'-diphenylmethane diisocyanate or toluene diisocyanate; and the catalyst is prepared by mixing dimethylcyclohexylamine and dimethylethanolamine in a mass ratio of 2-4:1.

[0025] Preferably, the molecular weight of polytetrahydrofuran is 800-1200.

[0026] Preferably, the method for preparing the filling layer material comprises the following steps:

[0027] The modified polyester material, the modified polyurethane material, the vulcanizing agent, magnesium oxide and the silane coupling agent are mixed at 150-170° C. for 15-30 minutes to obtain a mixture, and the mixture is transferred to a twin-screw extruder for extrusion, cooling, melting and drawing to obtain a filling layer material;

[0028] Wherein, the extrusion temperature is 150-170°C, and the screw speed of the twin-screw extruder is 100-150r / min.

[0029] The vulcanizing agent described in the present invention can be any commonly used vulcanizing agent without any particular limitation, such as tetramethylthiuram disulfide, benzoyl peroxide, etc.; the silane coupling agent described in the present invention can be any commonly used silane coupling agent without any particular limitation, such as silane coupling agent KH550, silane coupling agent KH560, silane coupling agent KH570, etc.

[0030] In a second aspect, the present invention provides a method for preparing the above-mentioned high-performance wind power generation cable, comprising the following steps:

[0031] An inner shielding layer, an insulating layer and an outer shielding layer are sequentially coated on the outer surface of the conductor to obtain a core wire. Multiple core wires are twisted along the cable axis to obtain a cable core. A filling layer is formed on the outer surface of the cable core. Finally, a tape and an outer sheath are sequentially coated on the outer surface of the filling layer to obtain a high-performance wind power generation cable.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention polymerizes 1,3-acetone dicarboxylic acid dimethyl ester and pentaerythritol under a catalyst to obtain a modified polyester material; the addition of citrate makes the modified polyester material have higher toughness; the modified plant nanofiber powder has a larger specific surface area and a unique nanoscale effect, and when added to the modified polyester material, the toughness and wear resistance of the modified polyester material can be improved; the synergistic effect of the two has a good toughening effect on the cable filling layer;

[0034] (2) The present invention adds plant nanofiber powder modified by a silane coupling agent when preparing the modified polyester material. Since hydrophobic groups are introduced on the surface of the fiber powder to form hydrophobic silicon-oxygen bonds, the surface energy of cellulose is reduced, the material's resistance to moisture is enhanced, and the stability and service life of the cable in a humid environment are improved;

[0035] (3) In the present invention, polytetrahydrofuran is selected as the soft segment when preparing the modified polyurethane material, which can improve the flexibility of the polyurethane material; the addition of modified cellulose introduces a hydrophobic ester group into the modified polyurethane, which helps to improve the waterproofness of the modified polyurethane;

[0036] (4) The high-performance wind power generation cable produced by the present invention has good tensile strength, high toughness, strong water resistance, and also has good torsion resistance and aging resistance. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is explained in detail below with reference to several representative embodiments of the present invention.

[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0039] Example 1

[0040] A method for preparing a filling layer material for a high-performance wind power generation cable is as follows:

[0041] (1) Preparation of modified wood nanofiber powder

[0042] 10g of wood nanofiber powder was mixed with 30mL of anhydrous ethanol, and then 6g of silane coupling agent KH550 was added, heated to 85°C and refluxed for 3h. After the reaction was completed, the modified wood nanofiber powder was dried;

[0043] (2) Preparation of modified polyester materials

[0044] 27.23 g (0.2 mol) of pentaerythritol, 76.62 g (0.44 mol) of dimethyl 1,3-acetone dicarboxylate (DTO), trimethyl citrate (2% m DTO ) were mixed evenly, stirred continuously and heated to 95°C for 1 h, and modified wood nanofiber powder (12% m DTO ) and tetrabutyl titanate (0.1% m DTO ) and then heated to 110°C for reaction for 6h, transferred to a mold, and vacuum cured at 110°C for 12h to obtain a modified polyester material;

[0045] (3) Preparation of modified cellulose

[0046] The crushed wheat straw was added to a 2 mol / L sodium hydroxide aqueous solution at a material-liquid ratio of 1:10 g / mL, heated to 95°C for reaction for 15 hours, washed with water 4 times, filtered, added to a 0.2 mol / L acetic acid aqueous solution at a material-liquid ratio of 1:15 g / mL, reacted at a temperature of 50°C for 8 hours, washed with water 3 times and dried to obtain modified cellulose;

[0047] (4) Preparation of modified polyurethane materials

[0048] 2g of modified cellulose, 10g of polytetrahydrofuran with a molecular weight of 800 and 1g of dodecanediamine were mixed, stirred and heated to 80°C, and after the solid was dissolved, 8g of 4,4'-diphenylmethane diisocyanate, 0.02g of dimethylcyclohexylamine and 0.01g of dimethylethanolamine were added to react for 6h, poured into a mold, and vacuum cured at 110°C for 9h to obtain a modified polyurethane material;

[0049] (5) Preparation of filling layer materials

[0050] 70g of modified polyester material, 30g of modified polyurethane material, 10g of tetramethylthiuram disulfide, 2g of magnesium oxide, and 4g of silane coupling agent KH550 were mixed at 160°C for 15min to obtain a mixture, and the mixture was transferred to a twin-screw extruder for extrusion, cooling, melting, and drawing to obtain a filling layer material;

[0051] The extrusion temperature is 170° C., and the screw speed of the twin-screw extruder is 110 r / min.

[0052] A method for preparing a high-performance wind power cable is as follows:

[0053] The inner shielding layer, insulating layer and outer shielding layer are sequentially coated on the outer surface of the conductor (taking the copper core as an example) to obtain a core wire. Multiple core wires are twisted along the cable axis to obtain a cable core. The outer surface of the cable core is filled to form a filling layer. Finally, the outer surface of the filling layer is sequentially coated with a tape and an outer sheath to obtain a high-performance wind power generation cable.

[0054] Example 2

[0055] A method for preparing a filling layer material for a high-performance wind power generation cable is as follows:

[0056] (1) Preparation of modified wood nanofiber powder

[0057] 10g of wood nanofiber powder was mixed with 30mL of anhydrous ethanol, and then 7g of silane coupling agent KH560 was added and heated to 90℃ and refluxed for 2.5h. After the reaction was completed, the modified wood nanofiber powder was obtained by drying.

[0058] (2) Preparation of modified polyester materials

[0059] 27.23 g (0.2 mol) of pentaerythritol, 55.73 g (0.32 mol) of dimethyl 1,3-acetone dicarboxylate (DTO), triethyl citrate (1.5% m DTO ) were mixed evenly, stirred continuously and heated to 90°C for 1 h, and modified wood nanofiber powder (13% m DTO ) and tetraisopropyl titanate (0.15% m DTO ) and then heated to 115°C for reaction for 7h, transferred to a mold, and vacuum cured at 115°C for 4h to obtain a modified polyester material;

[0060] (3) Preparation of modified cellulose

[0061] The crushed corn stalks were added to a 2 mol / L sodium hydroxide aqueous solution at a material-liquid ratio of 1:12 g / mL, heated to 90°C for reaction for 10 hours, washed with water 5 times, filtered, added to a 0.2 mol / L acetic acid aqueous solution at a material-liquid ratio of 1:18 g / mL, reacted at 60°C for 5 hours, washed with water twice, and dried to obtain modified cellulose;

[0062] (4) Preparation of modified polyurethane materials

[0063] 1g of modified cellulose, 12g of polytetrahydrofuran with a molecular weight of 900, and 2g of dodecanediamine were mixed, stirred and heated to 90°C, and after the solid was dissolved, 6g of 4,4'-diphenylmethane diisocyanate / 0.02g of dimethylcyclohexylamine and 0.01g of dimethylethanolamine were added to react for 7h, poured into a mold, and vacuum cured at 115°C for 10h to obtain a modified polyurethane material;

[0064] (5) Preparation of filling layer materials

[0065] 60g of modified polyester material, 20g of modified polyurethane material, 15g of tetramethylthiuram disulfide, 3g of magnesium oxide, and 1g of silane coupling agent KH570 were mixed at 150°C for 30min to obtain a mixture, and the mixture was transferred to a twin-screw extruder for extrusion, cooling, melting, and drawing to obtain a filling layer material;

[0066] The extrusion temperature is 160° C., and the screw speed of the twin-screw extruder is 120 r / min.

[0067] The method for preparing the wind power generation cable is the same as that in Example 1.

[0068] Example 3

[0069] A method for preparing a filling layer material for a high-performance wind power generation cable is as follows:

[0070] (1) Preparation of modified straw nanofiber powder

[0071] 10g of straw nanofiber powder was mixed with 30mL of anhydrous ethanol, and then 6g of silane coupling agent KH570 was added, heated to 85℃ and refluxed for 4h. After the reaction was completed, the modified straw nanofiber powder was obtained by drying.

[0072] (2) Preparation of modified polyester materials

[0073] 27.23 g (0.2 mol) of pentaerythritol, 69.66 g (0.4 mol) of dimethyl 1,3-acetone dicarboxylate (DTO), triethyl citrate (3% m DTO ) were mixed evenly, stirred continuously and heated to 110℃ for 1.5h, and modified straw nanofiber powder (10% m DTO ) and tetrapropyl titanate (0.08% m DTO ) and then heated to 130°C for reaction for 7h, transferred to a mold, and vacuum cured at 120°C for 15h to obtain a modified polyester material;

[0074] (3) Preparation of modified cellulose

[0075] The crushed wood blocks were added to a 2 mol / L sodium hydroxide aqueous solution at a material-liquid ratio of 1:15 g / mL, heated to 100°C for reaction for 20 hours, washed twice with water, filtered, added to a 0.2 mol / L acetic acid aqueous solution at a material-liquid ratio of 1:18 g / mL, reacted at 70°C for 10 hours, washed 4 times with water, and dried to obtain modified cellulose;

[0076] (4) Preparation of modified polyurethane materials

[0077] 1g of modified cellulose, 15g of polytetrahydrofuran with a molecular weight of 1000, and 1g of dodecanediamine were mixed, stirred and heated to 100°C, and after the solid was dissolved, 8g of toluene diisocyanate, 0.03g of dimethylcyclohexylamine and 0.01g of dimethylethanolamine were added to react for 8h, poured into a mold, and vacuum cured at 110°C for 8h to obtain a modified polyurethane material;

[0078] (5) Preparation of filling layer materials

[0079] 70 g of modified polyester material, 25 g of modified polyurethane material, 10 g of benzoyl peroxide, 1 g of magnesium oxide, and 2 g of silane coupling agent KH560 were mixed at 160° C. for 20 min to obtain a mixture, and the mixture was transferred to a twin-screw extruder for extrusion, cooling, melting, and drawing to obtain a filling layer material;

[0080] The extrusion temperature is 150° C., and the screw speed of the twin-screw extruder is 130 r / min.

[0081] The method for preparing the wind power generation cable is the same as that in Example 1.

[0082] Example 4

[0083] A method for preparing a filling layer material for a high-performance wind power generation cable is as follows:

[0084] (1) Preparation of modified straw nanofiber powder

[0085] 10g of straw nanofiber powder was mixed evenly with 30mL of anhydrous ethanol, and then 8g of silane coupling agent KH570 was added, heated to 80°C and refluxed for 2h. After the reaction was completed, the modified straw nanofiber powder was dried;

[0086] (2) Preparation of modified polyester materials

[0087] 27.23 g (0.2 mol) of pentaerythritol, 62.69 g (0.36 mol) of dimethyl 1,3-acetone dicarboxylate (DTO), tripropyl citrate (1% m DTO ) were mixed evenly, stirred continuously and heated to 100℃ for 2h, and modified straw nanofiber powder (15% m DTO ) and tetrabutyl titanate (0.12% m DTO ) and then heated to 120°C for reaction for 5h, transferred to a mold, and vacuum cured at 110°C for 12h to obtain a modified polyester material;

[0088] (3) Preparation of modified cellulose

[0089] The crushed bamboo chips were added to a 2 mol / L potassium hydroxide aqueous solution at a solid-liquid ratio of 1:15 g / mL, heated to 110°C for reaction for 15 hours, washed with water three times, filtered, added to a 0.2 mol / L oxalic acid aqueous solution at a solid-liquid ratio of 1:15 g / mL, reacted at 65°C for 10 hours, washed with water five times, and dried to obtain modified cellulose;

[0090] (4) Preparation of modified polyurethane materials

[0091] 3g of modified cellulose, 12g of polytetrahydrofuran with a molecular weight of 800, and 2g of dodecanediamine were mixed, stirred and heated to 95°C, and after the solid was dissolved, 10g of toluene diisocyanate, 0.04g of dimethylcyclohexylamine and 0.01g of dimethylethanolamine were added to react for 7h, poured into a mold, and vacuum cured at 120°C for 8h to obtain a modified polyurethane material;

[0092] (5) Preparation of filling layer materials

[0093] 80g of modified polyester material, 20g of modified polyurethane material, 15g of benzoyl peroxide, 5g of magnesium oxide, and 5g of silane coupling agent KH550 were mixed at 170°C for 20min to obtain a mixture, and the mixture was transferred to a twin-screw extruder for extrusion, cooling, melting, and drawing to obtain a filling layer material;

[0094] The extrusion temperature is 160° C., and the screw speed of the twin-screw extruder is 150 r / min.

[0095] The method for preparing the wind power generation cable is the same as that in Example 1.

[0096] Performance Testing

[0097] Relevant performance tests were performed on the wind power cables prepared in Example 1 to Example 4, as shown in Table 1.

[0098] Table 1 Performance test results of the embodiment

[0099]

[0100] It can be seen from Table 1 that the wind power generation cable prepared by the present invention has good mechanical properties, flame retardancy, water resistance, etc., and has excellent comprehensive performance.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that no modified wood nanofiber powder is added to the modified polyester material, and the rest is the same as Example 1.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that the modified wood nanofiber powder used in the modified polyester material is replaced with an equal amount of wood nanofiber powder, and the rest is the same as Example 1.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that no citrate is added to the modified polyester material, and the rest is the same as Example 1.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that the amount of modified cellulose added in the modified polyurethane material is different, as shown in Table 2, and the rest is the same as Example 1.

[0109] Table 2 Modified cellulose addition amount

[0110]

[0111] Table 3 Comparative Example Performance Test Results

[0112]

[0113] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the modified plant nanofiber powder prepared by the present invention mainly affects its toughness and water resistance. The modified plant fiber powder contains hydrophobic silicon-oxygen bonds, which enhances the water resistance of the material.

[0114] It can be seen from Example 1 and Comparative Example 3 that the addition of plasticizer citrate can increase the mobility of polymer molecular chains and enhance the elongation at break and tensile strength of the polymer.

[0115] It can be seen from Example 1 and Comparative Example 4 that the modified cellulose prepared by the present invention can improve the tensile strength and water resistance of the material; however, when the amount of modified cellulose added is too much, the tensile strength decreases, which may be caused by the aggregation of modified cellulose; at the same time, cellulose can generate hydrophobic ester groups with aromatic diisocyanates, which helps to improve the water resistance of modified polyurethane.

[0116] The pentaerythritol added when preparing the modified polyester material of the present invention can act as a cross-linking agent and have good flame retardant properties. At the same time, the modified plant nanofiber powder is added. The modified plant nanofiber powder has the advantages of small particle size and large specific surface area, plays a high reinforcement and high filling role in the rubber polyester material, increases the cross-linking density of the polymer, forms a more stable network structure, and cooperates with pentaerythritol to improve its flame retardant property and anti-dripping property.

[0117] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.

Claims

1. A wind power generation cable, characterized in that: The wind power generation cable comprises a core wire, the core wire comprises a conductor, the outer surface of the conductor is sequentially coated with an inner shielding layer, an insulating layer and an outer shielding layer along its own axis; a plurality of core wires are twisted along the cable axis to form a cable core, a wrapping tape and an outer sheath are sequentially arranged outside the cable core, and a filling layer is filled between the wrapping tape and the cable core; The filling layer material is made of the following raw materials in parts by weight: 60-80 parts of modified polyester material, 20-30 parts of modified polyurethane material, 10-15 parts of vulcanizing agent, 1-5 parts of magnesium oxide, and 1-5 parts of silane coupling agent; The preparation method of the modified polyester material comprises the following steps: (1) mixing plant nanofiber powder and anhydrous ethanol evenly, adding a silane coupling agent, heating and refluxing, and drying after the reaction to obtain modified plant nanofiber powder; (2) pentaerythritol, dimethyl 1,3-acetone dicarboxylate and citrate are uniformly mixed, the temperature is raised to carry out a first-stage reaction, the modified plant nanofiber powder and the catalyst are added, the temperature is continued to be raised to carry out a second-stage reaction, and the modified polyester material is obtained by vacuum curing; In the step (1), the mass ratio of plant nanofiber powder to silane coupling agent is 1:0.6-0.8; the reaction temperature is 80-90°C and the reaction time is 2-4h; In the step (2), the molar ratio of pentaerythritol to 1,3-acetone dicarboxylic acid dimethyl ester is 1:1.6-2.2; the amount of the citrate ester is 1%-3% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester, the amount of the modified plant nanofiber powder is 10%-15% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester, and the amount of the catalyst is 0.08%-0.15% of the mass of 1,3-acetone dicarboxylic acid dimethyl ester; the catalyst is tetrabutyl titanate, tetraisopropyl titanate, or tetrapropyl titanate; The preparation method of the modified polyurethane material comprises the following steps: 1-3 parts by mass of modified cellulose, 10-15 parts by mass of polytetrahydrofuran, and 1-2 parts by mass of dodecanediamine are uniformly mixed at a temperature of 80-100° C., and then 6-10 parts by mass of aromatic diisocyanate and 0.02-0.05 parts by mass of catalyst are added to react for 6-8 hours, and vacuum cured to obtain a modified polyurethane material; In the preparation method of the modified polyurethane material, the catalyst is prepared by mixing dimethylcyclohexylamine and dimethylethanolamine in a mass ratio of 2-4:1; The preparation method of the modified cellulose comprises the following steps: The plant cellulose is placed in an alkaline solution, heated to 90-110°C, reacted for 10-20 hours, washed with water 2-5 times, placed in an acidic solution at 50-70°C, reacted for 5-10 hours, washed with water 2-5 times, and dried to obtain modified cellulose; Wherein, the alkaline solution is a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution; The acidic solution is an oxalic acid aqueous solution or an acetic acid aqueous solution.

2. The wind power generation cable according to claim 1, characterized in that: In step (2), the citrate ester is trimethyl citrate, triethyl citrate or tributyl citrate.

3. The wind power generation cable according to claim 1, characterized in that: The aromatic diisocyanate is 4,4'-diphenylmethane diisocyanate or toluene diisocyanate.

4. The wind power generation cable according to claim 1, characterized in that: The preparation method of the filling layer material comprises the following steps: The modified polyester material, the modified polyurethane material, the vulcanizing agent, magnesium oxide and the silane coupling agent are mixed at 150-170° C. for 15-30 minutes to obtain a mixture, and the mixture is transferred to a twin-screw extruder for extrusion, cooling, melting and drawing to obtain a filling layer material; Wherein, the extrusion temperature is 150-170°C, and the screw speed of the twin-screw extruder is 100-150r / min.

5. A method for preparing a wind power cable according to claim 1, characterized in that: The steps include: An inner shielding layer, an insulating layer and an outer shielding layer are sequentially coated on the outer surface of the conductor to obtain a core wire. A plurality of core wires are twisted along the cable axis to obtain a cable core. A filling layer is formed on the outer surface of the cable core. Finally, a tape and an outer sheath are sequentially coated on the outer surface of the filling layer to obtain a wind power generation cable.

Citation Information

Patent Citations

  • Preparation method of filling layer material for cable of charging pile of electric car

    CN107353494A

  • High-toughness high-elasticity anti-hydrolysis polyurethane elastomer sizing material and production method thereof

    CN105315654A

  • Anti-torsion medium voltage flexible power cable used for wind power generation

    CN203931628U